Ten-year experience with transcatheter aortic valve implantation in bicuspid aortic valve: lessons learned and future perspectives - Walczewski, Michał; Gasecka, Aleksandra; Huczek, Zenon; Rymuza, Bartosz; Kochman, Janusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Bicuspid aortic valve (BAV) stenosis has traditionally been perceived as a contraindication to transcatheter aortic valve implantation (TAVI) due to its specific anatomical characteristics including extensive calcifications, high leaflet coaptation and frequently encountered aortic root dilation, which may result in worse procedural outcomes and higher risk of complications. Hence, BAV patients were not included in previous clinical trials. In the recent years, improved pre-procedural imaging and technological advances have gradually enabled expansion of TAVI to patients with complex anatomy, including those with BAV. Moreover, indications for TAVI are expanding to a younger group of patients with fewer comorbidities, and BAV is more prevalent in this population. Contemporary multicenter registry-based studies indicate that patients undergoing TAVI for BAV have similar outcomes as those with tricuspid aortic valve stenosis. In this article, we provide a thorough overview of the available clinical data regarding the outcomes of TAVI in BAV, from the perspective of an experienced TAVI center with over 150 TAVIs in this group of patients, performed in our institution since the year 2009. We present anatomical and clinical classifications of BAV, differences in outcomes in patients with bicuspid and tricuspid valves, as well as important topics regarding choice of an adequate valve and valve size.